To find the derivative of the function given we can use the product rule and the quotient rule.
Product rule:
The product rule states that:
![(d)/(dx)(fg)=g(df)/(dx)+f(dg)/(dx)](https://img.qammunity.org/2023/formulas/mathematics/high-school/ew8zffazlwnagd79aa0c3hp0855uvzxz5u.png)
Then, for the function given we have:
![\begin{gathered} (d)/(ds)\lbrack(s^3+4)(4s^2+6)\rbrack=(4s^2+6)(d)/(ds)(s^3+4)+(s^3+4)(d)/(ds)(4s^2+6) \\ =(4s^2+6)(3s^2)+(s^3+4)(8s) \\ =12s^4+18s^2+8s^4+32s \\ =20s^4+18s^2+32s \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/cp2lpnsdeboyj3i82e04tklr0jpv7dnkrx.png)
therefore the derivative is:
![(dg)/(ds)=20s^4+18s^2+32s](https://img.qammunity.org/2023/formulas/mathematics/high-school/7jgokjn6yeo9glf9tjkgcud5kf04oe50zt.png)
Quotient rule:
To use the quotient rule we need to write the function in the following way:
![g(s)=(s^3+4)/((4s^2+6)^(-1))](https://img.qammunity.org/2023/formulas/mathematics/high-school/dklrq12obq5ivci2zb57cjl1vtxr7pet62.png)
Now, the quotient rulre states that:
![(d)/(dx)((f)/(g))=(g(df)/(dx)-f(dg)/(dx))/(g^2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/4smx42i9n6vs2mwna2ohh0xpgzoqdoaw5z.png)
Then, in our case we have:
![\begin{gathered} (d)/(ds)((s^3+4)/((4s^2+6)^(-1)))=((4s^2+6)^(-1)(d)/(ds)(s^3+4)-(s^3+4)(d)/(dx)(4s^2+6)^(-1))/(\lbrack(4s^2+6)^(-1)\rbrack^2) \\ =\frac{(4s^2+6)^(-1)(3s^2)-(s^3+4)\lbrack-(4s^2+6)^(-2)\rbrack^{}(8s)}{\lbrack(4s^2+6)^(-1)\rbrack^2} \\ =((3s^2)/(4s^2+6)+(8s(s^3+4))/((4s^2+6)^2))/(\lbrack(4s^2+6)^(-1)\rbrack^2) \\ =((1)/(4s^2+6)(3s^2+(8s^4+32s)/(4s^2+6)))/(\lbrack(4s^2+6)^(-1)\rbrack^2) \\ =((1)/(4s^2+6)((3s^2(4s^2+6)+8s^4+32s)/(4s^2+6)))/(\lbrack(4s^2+6)^(-1)\rbrack^2) \\ =((1)/(4s^2+6)((12s^4+18s^2+8s^4+32s)/(4s^2+6)))/(\lbrack(4s^2+6)^(-1)\rbrack^2) \\ =((1)/(4s^2+6)((20s^4+18s^2+32s)/(4s^2+6)))/(\lbrack(4s^2+6)^(-1)\rbrack^2) \\ =((20s^4+18s^2+32s)/((4s^2+6)^2))/((1)/((4s^2+6)^2)) \\ =((4s^2+6)^2(20s^4+18s^2+32s))/((4s^2+6)^2) \\ =20s^4+18s^2+32s \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/svqyn2dm1v31y3yaena3rnfik4s025b7en.png)
therefore the derivative is:
![(dg)/(ds)=20s^4+18s^2+32s](https://img.qammunity.org/2023/formulas/mathematics/high-school/7jgokjn6yeo9glf9tjkgcud5kf04oe50zt.png)
(Notice how we get the same result as before)